Environmental licensing of renewable energies in Ceará (Research, Society and Development, 2022)
Brazil adopted the simplification of environmental licensing for energy production, in order to meet its goal in international agreements for energy transition. Ceará was one of the states that developed specific standards related to activities. Thus, the objectives of this article were to present the quantitative of environmental licenses related to wind and solar sources between 2011 and 2021, map the licensed enterprises in Ceará, Brazil, and Describe the related regulations and present the challenges and measures taken within the state environmental agency (SEMACE). The number of processes and licenses issued was raised through SEMACE’s digital systems, in addition to the regulations published in the period. The challenges and the proposition of management measures were presented from the experience of environmental analysts, who followed the actions and procedures over the years. As verified, most of the environmental permits issued referred to wind energy, totaling 348 approved projects, located mainly in the coastal zone. On the other hand, 128 licenses were issued, only in 2021, for solar photovoltaic projects, located in different meso-regions of Ceará. It is concluded that the revision of the standards and regulations for the state environmental licensing collaborated for a better planning and management of the licensing. However, there is a need to implement some improvements in digital systems, in addition to conducting studies that can support the establishment of public policies and environmental control measures that are effective in the implementation of energy projects.